A case of multifocal skin metastases from lung cancer presenting with vasculitic-type cutaneous nodule - Nalan Akgul Babacan; Saadettin Kiliçkap; Soner Sene; Turgut Kacan; Birsen Yucel; Mehmet Fuat Eren; Sener Cihan (Wolters Kluwer Medknow Publications, 2015)
Although cutaneous metastasis occurs usually at the terminal stage of the disease, it may be rarely concurrent with the diagnosis and may also present as the first sign of the illness. A 55-year-old male patient presented with vasculitic-type cutaneous nodular lesions and a necrotic distal phalangeal lesion developed over the last month. He was a tradesman and smoked 40 packets year. On physical examination, he was found to have multiple cutaneous lesions on the skin of the face, limbs, neck, scalp, dorsal side, fingers, subungual side, right leg, and feet. A skin lesion punch biopsy was performed and squamous cell carcinoma metastasis was detected. He was diagnosed as having squamous cell lung cancer with bronchoscopic biopsy. Although it is very rare, cutaneous metastases that is concurrent with the diagnosis of lung cancer may be the first sign of the disease. In patients with suspicious skin lesions, the patient's age, smoking history, and other symptoms should be evaluated and a biopsy should be performed.